á¹¬AHA HUSAIN'S SKEPTICISM OF Já¾¹HILÄª POET AND ITS POSITION IN THE QUR'AN: ANALYSIS OF á¹¬AHA HUSAIN'S THOUGHT IN FÄª AL-SYI'RI AL-JÄ€HILÄª - Faruq, Umarul; Riyadi, Abdul Kadir (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
á¹¬aha Husain has an educational background in Egypt and Paris, so it is not surprising that he sometimes adopts the methods of orientalist scepticism that he admires many while in Paris. However, he still paid attention to Egypt. As the father of literature at this time, he paid attention to popular Arabic literature, namely the poetry jahili, which he later booked, and he named FÄ« al-Syi'rÄ« al-JÄhilÄ«, which later changed its name to FÄ« al-AdÄb al-JÄhilÄ«. With qualitative methods and data excavation categorized as research libraries, the author tried to reveal how Taha Husain's study of Arabic literature is contained in his work FÄ« al-Syi'ri al-JÄhilÄ«. This research resulted in the fact that the poem jahili, according to á¹¬aha, is no longer authentic. It has been infiltrated by some interests, both personal, tribal fanaticism, politics, and even religion. Even if there is still genuine poetry, then it is very little. This authenticity made Taha refuse and said that this no longer authentic poetry could not be used as a tool to understand the Qur'an. It must be the other way around because the Qur'an is the only original and most reliable Arabic literature.